Impact of Mar`ke Bilar healthy drink on blood levels of malondialdehyde, superoxide dismutase, and hemoglobin in soccer athletes at PPLP North Sumatra - Siahaan, G.; Widodo, E.; Lestrina, D.; Oppusunggu, R. (Asian Journal of Sports Medicine, 2024)
Background:High-intensity soccer activities due to overtraining can cause the emergence of reactive oxygen species (ROS), resulting in an imbalance of free radicals in the form of malondialdehyde (MDA) and endogenous antioxidants in the form of superoxide dismutase (SOD). As a result, it can interfere with the formation of hemoglobin (Hb) needed by an athlete to take in oxygen (VO2max).